Wage effects of high-skilled migration: International evidence - Volker Grossmann; David Stadelmann (Institute for the Study of Labor (IZA), 2012)
This paper argues that international migration of high-skilled workers triggers productivity effects at the macro level such that the wage rate of skilled workers may rise in host countries and decline in source countries. We exploit a recent data set on international bilateral migration flows and provide evidence which is consistent with this hypothesis. We propose different instrumentation strategies to identify the causal effect of skilled migration on log differences of GDP per capita, total factor productivity, and wages of skilled workers between pairs of source and destination countries. These address the endogeneity problem which potentially arises when international wage differences affect migration decisions.
Keywords: F22; O30; 330; international high-skilled migration; wage effects; total factor productivity; Brain Drain; Hochqualifizierte Arbeitskräfte; Lohnniveau; Produktivität; OECD-Staaten